2016
DOI: 10.1186/s13052-016-0244-9
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 gene polymorphisms in Egyptian children with febrile seizures: a case–control study

Abstract: BackgroundFebrile seizures are the most common form of childhood seizures. Among pro-inflammatory cytokines, interleukin-6 is the key acute-phase cytokine. To date, only a few studies concerned the association of interleukin-6 gene polymorphisms with febrile seizures.In this study, we aimed to investigate 3 cytokine single-nucleotide polymorphisms situated at positions –174 (G/C), –572 (G/C), and –597 (G/A) in the promoter region of the interleukin-6 gene for the first time in Egyptian children with febrile se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…IL-6 is a cell signaling molecule that has been associated with many diseases, including inflammatory, neurological, vascular, and malignant processes [ 21 ]. The systemic concentration of IL-6 is mainly regulated at the level of expression, because IL-6 is rapidly cleared from the plasma and has a short plasma half-life of 20–60 min [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is a cell signaling molecule that has been associated with many diseases, including inflammatory, neurological, vascular, and malignant processes [ 21 ]. The systemic concentration of IL-6 is mainly regulated at the level of expression, because IL-6 is rapidly cleared from the plasma and has a short plasma half-life of 20–60 min [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their findings revealed that the patient group was more susceptible to FS. In addition, they reported a negative association between FSs and the C allele at the À174 position, indicating that this association could represent a protective effect against FSs [29].…”
Section: Discussionmentioning
confidence: 98%
“…The studies reported protein levels in serum or CSF and compared them with those of controls. We conducted meta-analyses of serum IL-1b levels based on five studies [10,19,23,25,28], CSF IL-1b based on two studies [10,28], serum TNF-a based on two studies [23,28] and serum IL-6 based on two studies [23,29]. The cytokine levels of patients and controls were expressed in pg/ml and significant difference was shown in P-value.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Consistent with the notion that elevated IL-6 is associated with seizures in patients with ESES, immunomodulation that reduced IL-6 levels also improved electroencephalographic seizure activity [150]. IL-6 gene polymorphisms have also been implicated in pediatric epilepsy and febrile seizure cases [149,[151][152][153]. Transgenic mice that expressed elevated astrocytic IL-6 were more susceptible to NMDA-induced seizures and sub-threshold doses of kainic acid [154], with the latter causing mice to have severe tonic-clonic seizures and death.…”
Section: Il-6 Elevation Is Associated With Epileptogenesismentioning
confidence: 75%